Synthesis of Mn-Doped Fe-MOFs with Different Ratios and Its Application for Photocatalytic Degradation of Rhodamine B Dye - Kim Ngan Thi Tran; Thuy Bich Tran; Sy Trung Do; Kim Oanh Thi Nguyen; Tan Van Lam (Universitas Gadjah Mada, 2022)
Recent trends in environmental remediation have shifted to the use of metal-organic framework (MOF) composites due to their unique structural properties. It is still challenging to diversify MOFs photocatalysts to fulfill application to treat toxic organic pigments. In this study, Fe-MOF bimetallic materials were synthesized by doping Mn2+ ions at different ratios. The structural and morphological characteristics of the materials were analyzed by XRD, UV-Vis, FT-IR, SEM, and UV-Vis DRS methods. Mn/Fe-MOF bimetallic organic framework materials were used to evaluate the photocatalytic degradation of Rhodamine B (RhB) dyes. The results show that, under the same experimental conditions, the RhB degradation efficiency of Mn/Fe-MOF is enhanced than that of the pristine Fe-MOF catalyst under the influence of visible light. After 120 min, the RhB solution was decomposed to 91.78% by combining 0.1 Mn/Fe-MOF, H2O2, and visible light irradiation. At the same time, the presence of H2O2 in the reaction system also showed a strong impact on the efficiency of RhB degradation. The activity from the two metal centers of Mn/Fe-MOF contributes to the formation of a unique structure and composition that can be used as a photocatalyst for colored wastewater treatment.